Knowledge, attitudes, and practice of pelvic floor dysfunction and pelvic floor ultrasound among women of childbearing age in Sichuan, China - Wu, Xiaoli; Yi, Xiaohong; Zheng, Xiu; Chen, Zeling; Liu, Junxi; Dai, Xiong (Frontiers in Public Health, 2023)
Objective: Pelvic floor dysfunction (PFD) is highly prevalent among women. Pelvic floor ultrasound (PFU) is a critical method for assessing PFD. This study examined the knowledge, attitudes, and practice (KAP) of women of childbearing age regarding PFD and PFU. Methods: This cross-sectional study was conducted between August 18, 2022, and September 20, 2022, in Sichuan, China. A total of 504 women of childbearing age participated in this study. A self-administered questionnaire was developed to assess KAP regarding PFD and PFU. Univariable and multivariable logistic regression analyses were conducted to assess the association between demographic characteristics and KAP. Results: The average scores for knowledge, attitudes, and practice were 12.53, 39.98, and 16.51 out of 17, 45, and 20, respectively. Despite adequate knowledge of PFD symptoms, aging-related risks, and PFD harms (correct rates > 80%), participants showed poor knowledge about the benefits of PFU, PFU types, and Kegel exercise (correct rates < 70%). High scores in knowledge and attitude (odds ratio = 1.23 and 1.11, P < 0.001 and P = 0.005, respectively) were independent predictors of good practice, while never having been pregnant (odds ratio = 0.10, P < 0.001), alcohol consumption (odds ratio = 0.09, P = 0.027), and not being diagnosed with PFD or an unclear diagnosis independently predicted poor practice (both odds ratio = 0.03, both P < 0.001). Conclusion: Women of childbearing age in Sichuan, China, showed moderate knowledge, positive attitude, and good practice regarding PFD and PFU. Knowledge, attitude, pregnancy history, alcohol consumption, and PFD diagnosis are associated with practice.